Adaptability of oilseed species at high altitudes of Colorado and technology transfer to Afghanistan - Sediqi, Mohammad Navid, author; Johnson, Jerry J., advisor; Byrne, Patrick F., committee member; Jha, Ajay K., committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: adaptability of oilseed species; flax; growing degree day (GDD); high altitude; oil composition and fatty acid content; technology transfer